Measuring the latency of crimes committed with the help of information and communication technologies according to the matrix of A.A. Konev's punishability indices - Komarov, Anton Anatolevich (Вопросы безопасности, 2024)
The subject of the study in this paper is the real state of computer crime. At the moment, this type of crime is one of the most urgent problems of national security. Its qualitative and quantitative indicators indicate the need to reorient the activities of law enforcement agencies to combat this threat. However, in our opinion, such a reorientation should correspond to a balanced analysis and understanding of the true state of affairs not only in the accounting and registration discipline of law enforcement agencies engaged in countering such socially dangerous encroachments, but also in the actual state of its latent part. The main difficulty in such an analysis is that the completeness of criminal statistics on the issue of computer crime is provided for a fairly short period of time. Therefore, within the framework of our work, special attention is paid to the applied mathematical and statistical aspects of the accounting and registration discipline of law enforcement entities, as a necessary condition for its objective knowledge, in order to plan law enforcement activities more effectively.  To solve the tasks assigned to us, we resorted to the use of the documentary method in our research. After that, the data was statistically processed by summarizing and grouping. Then the hypotheses of the study were verified by mathematical calculations of the indices of punishability, the intensity of the manifestation of public danger and the severity coefficients of computer crime according to the original methodology of A.A. Konev. The main conclusions of this study are the statements that there has been no qualitative change in the degree of latency of computer crime, despite its multiple increase in volumes. At the same time, it is obvious that the latency of certain types of computer crimes is not uniform and varies in different ways, depending on the structure. The actual state of computer crime depends on many mediating factors. But the calculation model indicates the need for two indispensable conditions: an increase in the severity of acts and a multiplicity of volume growth rates over a relatively short period of time, as a necessary component of reducing the latent part of crime. Such conditions in the framework of computer crime are observed only in two cases: Internet drug crime related to the retail sale of prohibited substances and mercenary computer crimes are primarily frauds.